Sestavljene narodne identitete v romanu Eveline Umek Zlata poroka ali Tržaški blues - Stekar, Daniela (Jezik in slovstvo, 2015)
In terms of methodology, the present article is based on literary imagology and autobiographic methodology. The object of the study was Evelina Umek's novel The Golden Wedding or The Blues of Trieste) (Zlata poroka ali Tržaški blues), in which many characters with a composite identity were identified. A composite national identity typology was defined and used as the basis for the typological definition of the literary subjects of the novel. The argumentation was based on the basic definitions of national identities by postcolonial theorist Homi K. Bhabha and social psychologist John W. Berry. The continuation focuses on the composite identity of the Slovenian fictional characters living in Trieste, comparing them with the fixed Slovenian identity type. It was concluded that the fictional characters who identify themselves more with Slovenes are depicted more positively than those predominantly assuming an Italian identity: the more Italian their identity, the more they are portrayed in a negative light.
Keywords: Umek, Evelina, 1939-; "Zlata poroka ali Tržaški blues"; Slovene literature; slovenska književnost; slovenska zamejska književnost; kratka proza; avtobiografska metoda; narodna identiteta